Talent management and intention to~stay in the mining industry: A~moderation mediation model of~workplace flexibility and organisational commitment - William Makumbe (Rajagiri Management Journal (RAMJ), 2025)
The mining industry is driving the growth of global economies; however, the sector faces persistent talent retention challenges. This research sought to investigate the impact of intervening variables on the relationship between talent management practices (TMP) and intention to stay.Statistical analysis was conducted using SmartPLS4, with data systematically collected from 380 participants.The results suggested that whilst organisational commitment partially mediates the relationship between TMP and intention to stay, workplace flexibility positively moderates the relationship between the two variables.Little is empirically known about the moderating role of workplace flexibility on the relationship between talent management and organisational commitment in the SADC mining industry. This study presents a validated model that facilitates managerial decision-making.
Keywords: 650; Talent management practices; Intention to stay; Workplace flexibility; Organisational commitment; Mining industry